2013
DOI: 10.1371/journal.pone.0071845
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory and Metabolic Networks for the Adaptation of Pseudomonas aeruginosa Biofilms to Urinary Tract-Like Conditions

Abstract: Biofilms of the Gram-negative bacterium Pseudomonas aeruginosa are one of the major causes of complicated urinary tract infections with detrimental outcome. To develop novel therapeutic strategies the molecular adaption strategies of P. aeruginosa biofilms to the conditions of the urinary tract were investigated thoroughly at the systems level using transcriptome, proteome, metabolome and enzyme activity analyses. For this purpose biofilms were grown anaerobically in artificial urine medium (AUM). Obtained dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 132 publications
(161 reference statements)
1
33
0
Order By: Relevance
“…Our results are in good agreement with the findings of Tielen et al who showed that P. aeruginosa PAO1 is not able to grow on urea as a sole carbon source in AUM (21). Various secreted or surface-exposed virulence factors of P. aeruginosa could be involved in immune evasion, that is, elastase (LasB), alkaline metalloprotease (AprA), insulin cleaving membrane proteinase (ICMP), elongation factor Tu (EF-Tu), as well as in iron acquisition, that is, PvdS-regulated endoprotease (PrpL) and siderophores.…”
Section: Iron Was Identified As One Of the Major Limiting Factors Insupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are in good agreement with the findings of Tielen et al who showed that P. aeruginosa PAO1 is not able to grow on urea as a sole carbon source in AUM (21). Various secreted or surface-exposed virulence factors of P. aeruginosa could be involved in immune evasion, that is, elastase (LasB), alkaline metalloprotease (AprA), insulin cleaving membrane proteinase (ICMP), elongation factor Tu (EF-Tu), as well as in iron acquisition, that is, PvdS-regulated endoprotease (PrpL) and siderophores.…”
Section: Iron Was Identified As One Of the Major Limiting Factors Insupporting
confidence: 93%
“…6) and taken up by transporters such as an amino acid ABC transporter, which appeared to be highly abundant in the catheter biofilm (Table I). This hypothesis is supported by the finding that P. aeruginosa PAO1 is able to grow in AUM with peptone as the sole carbon source (21).…”
Section: Iron Was Identified As One Of the Major Limiting Factors Inmentioning
confidence: 76%
See 1 more Smart Citation
“…Correspondingly, NorCBQ and NosZY proteins were detected 30 -60 min after the shift (supplemental Table S4). This abundance pattern suggests a fine-tuned regulatory network with (i) nitrite formed by Nap most likely triggering nir gene expression and (ii) the nitrite reduction product NO initiating expression of nor and nos genes as described for P. aeroginosa (30). Furthermore, direct reduction of nitrite prevents its intermediary accumulation, thereby avoiding accumulation of toxic nitrite levels.…”
Section: Shibae Dfl12mentioning
confidence: 73%
“…Pairwise comparisons of obtained expression rates for different time points after the shift to anoxic conditions with data obtained prior to anaerobic shift (0 min) were made ( Table 1). The investigated time points were 5,10,15,20,30,60, and 120 min after the oxygen supply was switched off (Fig. 1).…”
Section: Chemostat Cultivation Of D Shibae Dfl12mentioning
confidence: 99%